2007
DOI: 10.1073/pnas.0607620104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Abcc6 as the major causal gene for dystrophic cardiac calcification in mice through integrative genomics

Abstract: The genetic factors contributing to the complex disorder of myocardial calcification are largely unknown. Using a mouse model, we fine-mapped the major locus (Dyscalc1) contributing to the dystrophic cardiac calcification (DCC) to an 840-kb interval containing 38 genes. We then identified the causal gene by using an approach integrating genetic segregation and expression array analyses to identify, on a global scale, cis-acting DNA variations that perturb gene expression. By studying two intercrosses, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(135 citation statements)
references
References 39 publications
3
132
0
Order By: Relevance
“…We therefore hypothesized that one of these deletions might contribute to the observed deficiency in MRP6 expression. Meng et al (18) previously found no effect of the 10-bp deletion on the mRNA stability, therefore excluding this deletion as causal mutation for DCC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We therefore hypothesized that one of these deletions might contribute to the observed deficiency in MRP6 expression. Meng et al (18) previously found no effect of the 10-bp deletion on the mRNA stability, therefore excluding this deletion as causal mutation for DCC.…”
Section: Discussionmentioning
confidence: 92%
“…MRP6 is mainly expressed in the liver and to a lesser extent in kidney. In contrast, very low levels have been found in tissues affected by dystrophic calcification, such as heart and muscle (18,21,22). Thus, the preventive mechanism of Abcc6 on cardiac calcification seems to be mediated by systemic rather than tissue-specific factors.…”
Section: Discussionmentioning
confidence: 99%
“…Dyscalc1 is a major contributor to dystrophic cardiovascular calcification in susceptible strains, affecting both the vessels and myocardium (8). Two genes have been independently implicated in Dyscalc, Abcc6 and Emp3 (9,10). Both genes were excluded as accounting for dMOD1 gene using known disease-associated polymorphisms and finding that both parental strains had the susceptible alleles of each gene (data not shown).…”
Section: F 2 Mice Display An Intermediate Phenotype Between the Two Pmentioning
confidence: 99%
“…In addition, deficiency in CD73 (encoded by the NT5E gene) causes a human disease called arterial calcifications due to deficiency in CD73 (ACDC), which is characterized by a spontaneous and premature onset of arterial calcification, closely related but phenotypically different from GACI and PXE [12]. Finally, mutations in the mouse ABCC6 gene have been associated with dystrophic cardiac calcification (DCC), a disease characterized by hydroxyapatite deposition in necrotic myocytes [13,14]. ABCC6 is expressed in the basolateral membrane of hepatocytes and in the proximal kidney tubules [15,16].…”
Section: Introductionmentioning
confidence: 99%